Outcome analysis for prediction of early and long-term survival in patients receiving intra-aortic balloon pumping after cardiac surgery - Kamiya, Hiroyuki; Schilling, Maximilian; Akhyari, Payam; Ruhparwar, Arjang; Kallenbach, Klaus; Karck, Matthias; Lichtenberg, Artur (General thoracic and cardiovascular surgery, 2016)
Patients requiring an intra-aortic balloon pump (IABP) after cardiac surgery are critically ill and need a prolonged ICU stay. Considering limited health care resources, the early identification of patients with an extremely poor prognosis is important as a solid base for the decision whether further aggressive continuation or cessation of the therapy is recommendable.
Gesehen am 07.05.2020